Biventricular Pressure-Volume Loop Assessment Before and After Pulmonary Valve Replacement in Tetralogy of Fallot. Issue 5 (7th September 2022) - Binka, Edem; Zhang, Jin; Seemann, Felicia; Jani, Vivek; Barnes, Benjamin; Gaur, Lasya; Lima, Joao A.C.; Ambale Venkatesh, Bharath; Carlsson, Marcus; Kutty, Shelby
Abstract : Patients with tetralogy of Fallot (TOF) may undergo pulmonary valve replacement (PVR) after initial full repair. We investigated indices of biventricular function, work and efficiency of TOF patients' using noninvasive pressure-volume (PV) loop analysis on cardiovascular magnetic resonance (CMR) images and compared pre-and post PVR groups. Biventricular segmentations of steady state free precession CMR images were performed using custom validated software (Segment version 2.0 R7067). Brachial cuff pressure estimated left ventricular (LV) systolic pressure. Right ventricular (RV) inputs were obtained from pre-PVR cardiac catheterization data. Biventricular PV loops were then derived using a time-varying elastance model. Twenty seven patients were studied: (22 pre-PVR, 5 post-PVR), mean age of 20±10.5 years and 83% male. RV stroke volume significantly differed before and after PVR (73.2±25 ml vs. 41±10 mL, P =0.01). RV stroke work (SW) and mean external power (MEP) were significantly less post-PVR, but there were no significant differences in the LV hemodynamic indices. TOF patients have reduced RV SW and MEP post-PVR suggesting improved hemodynamics. Noninvasive biventricular PV loop analysis shows potential for integration into standard CMR imaging of TOF and provides hemodynamic data that could influence management decisions.